Power and efficiency optimization of open Maisotsenko-Brayton cycle and performance comparison with traditional open regenerated Brayton cycle. (1st August 2020) - Chen, Lingen; Shen, Jiafeng; Ge, Yanlin; Wu, Zhixiang; Wang, Wenhua; Zhu, Fuli; Feng, Huijun
Highlights: Open Maisotsenko-Brayton cycle model is established. Finite time thermodynamics is applied by considering pressure drop loss. Maximum power output and parameter effects are obtained. The corresponding optimal mass flow rate of working fluid is also obtained. Performance of open Maisotsenko-Brayton cycle is more superior to that of traditional one. Abstract: The search for higher power and efficiency has been the main purpose of studying the Brayton cycle. Maisotsenko-cycle is one of the most promising heat recovery technologies for improving cycle thermodynamic efficiency and reducing pollution of Brayton cycles at present. Finite time thermodynamics is a powerful tool for optimizing various processes and cycles. An open Maisotsenko-Brayton cycle (Maisotsenko air saturator combined with the Brayton cycle) model is established by using finite time thermodynamics theory and considering the size constraints of real plant in this paper. Some important parameter expressions such as power output and efficiency are derived by considering the seven pressure drop losses in the intake, compression, expansion, discharge processes, two sides of Maisotsenko air saturator and flow process in the piping caused by the working fluid in the circulation, heat transfer loss to the ambient, irreversible losses in the compressor and turbine, and irreversible combustion loss in the combustor. The power is optimized by adjusting the mass flow rate of the working fluid and the distribution of pressure drop loss along the flow path. All other relative inlet pressure drops is related to relative inlet pressure drop at the compressor inlet. There exists an optimal relative inlet pressure drop at the compressor inlet (it corresponds to an optimal mass flow rate of the working fluid) which leads to maximum power, which classical thermodynamics analysis does not find. The maximum power output and the corresponding optimal relative inlet pressure drop at the compressor inlet are obtained besides the optimal pressure ratio of compressor in the cycle, which is also found in classical thermodynamic analysis. Effects of the mass flow rate of the water injected to the cycle, the relative pressure drop at the compressor inlet, the cycle temperature ratio and the cycle pressure ratio on cycle performance are analyzed by using numerical examples. The performances of the open Maisotsenko-Brayton cycle and traditional open regenerated Brayton cycle are compared, and the results show that both the power and efficiency performances of open Maisotsenko- Brayton cycle are higher than those of traditional open regenerated Brayton cycle.